Impact of Zakat Distribution as a Reduction In Poverty Case Study in the Province of West Sumatra - Dian Fitriarni Sari; Irfan Syauqi Beik; Wiwiek Rindayanti (International Journal of Zakat, 2019)
West Sumatra Province has a high Muslim population and also has a high amount of zakat funds even though it is not yet potential. Regulation of zakat which is different from other provinces in West Sumatra is the existence of compulsory zakat regulations which are directly deducted from salaries for the State Civil Apparatus (ASN). This has a positive impact on the collection of zakat funds in West Sumatra. This should be accompanied by the application of good zakat to reduce poverty. This study used questionnaire to obtain primary data in the province of West Sumatera. This study had 200 respondents, uses poverty indicators and the average time taken to exit poverty as an analysis tool. The results of this study indicate that zakat can be an instrument to reduce poverty, by empowering zakat effectively and increasing economic growth. This research also proves more concisely when the poor can exit of poverty if compared with the absence of zakat application. As for the implications given in this study, the government is expected to be able to support the existence of zakat as an instrument to reduce poverty and achieve the fulfillment of the potential of zakat which is maximized in the collection.